The effect of N2-fixing bacteria and split time application on growth of Oryza sativa - Tuan Mohd Razali, Tuan Syaripah Najihah (2013)
Rice plant or its scientific name, Oryza sativa is the staple food of Malaysia. Rice (Oryza sativa L.) is one of the most important food crops in the world and more than 90% of rice is produced and consumed in Asia. In order to increase the production of this crop, various methods have been done including the use of plant growth-promoting rhizobacteria (PGPR). Plant growth- promoting rhizobacteria (PGPR) are defined as root-colonizing bacteria that exert beneficial effects on plant growth and development. Nitrogen fertilizer is also used widely in rice plant production. But, only little nitrogen is absorbed by the plant and the rest is loss. The efficiency of the urea-N in rice culture is very low, generally around 30–40%, in some cases even lower. It is such a waste of input for not applying this fertilizer and bacteria at the correct time. Therefore this experiment is conducted to observe the effect of N2-fixing bacteria on rice plant and split time application on rice plant and to determine if there is any interaction between nitrogen fertilizer and split time application of N2-fixing bacteria on the growth of rice plant. Five treatments including one control with 6 replications were used in this experiment and are arranged by using RCBD. The nitrogen fertilizer was applied at the beginning of experiment while the N2-nitrogen fixing bacteria (UPMB10) was applied on 15th, 30th, 45th, 60th day after planting. The results showed that Bacillus sphaericus (UPMB10) increase the rice plant’s dry weight by 10.81%, root volume by 23.18%, root length by 9.93%, root surface area by 13.7% and nitrogen content by 4.36%. The most effective time to inoculate this bacteria is on the 45th day after planting. An early inoculation time did not give any advantage to the growth response of O. Sativa.